Teaching Science Education in Nigeria Universities for Innovation, Group Collaboration, Job Creation, Accessing Bank Loans and Creative Society for Young Inventors - B. G. Aregbesola; I. A. Ojelade; D. T. Haastrup (Research Parks Publishing LLC, 2023)
This paper examined the necessity for teaching science education in Nigeria universities for innovation, group collaboration, job creation, accessing bank loans and creative society for young inventors. It maintains that universities should be robust institutions where students will be able to diversify their knowledge into creativity and innovation. It also emphasized that innovation and creativity are driving forces to productivity which involve applying creative ideas to practical solutions and bringing them to market implementation. It links innovation and creativity to valuable assets and skills that could be fostered and developed in individuals and within institutions. The paper buttresses on need for collaboration among science education postgraduate students as it has a way to encourage innovation and creativity, that is when individuals with a diverse range of skills and backgrounds come together, it leads to the exchange of unique perspectives and ideas. It emphasizes aims to prepare the mindset of postgraduate students during the course work towards innovation and creativity, to set a pace for job creation for the present and future generations. And seeks the supports of banks with access to loans for set-up capital among others. Therefore, conclusion was made that teaching science education in Nigeria universities optimizes innovation, group collaboration, job creation, accessing bank loans and creative society for young inventors. Thus, the paper recommends among others that, postgraduate students should as a matter of urgency be schooled to perceive science education in Nigeria universities as relate to innovation and creativity and should be helped to see knowledge as a products and services.